Antibody screening using a human iPSC‐based blood‐brain barrier model identifies antibodies that accumulate in the CNS. Issue 9 (30th July 2020) - Georgieva, Julia V.; Goulatis, Loukas I.; Stutz, Charles C.; Canfield, Scott G.; Song, Hannah W.; Gastfriend, Benjamin D.; Shusta, Eric V.
Abstract: Drug delivery across the blood‐brain barrier (BBB) remains a significant obstacle for the development of neurological disease therapies. The low penetration of blood‐borne therapeutics into the brain can oftentimes be attributed to the restrictive nature of the brain microvascular endothelial cells (BMECs) that comprise the BBB. One strategy beginning to be successfully leveraged is the use of endogenous receptor‐mediated transcytosis (RMT) systems as a means to shuttle a targeted therapeutic into the brain. Limitations of known RMT targets and their cognate targeting reagents include brain specificity, brain uptake levels, and off‐target effects, driving the search for new and potentially improved brain targeting reagent‐RMT pairs. To this end, we deployed human‐induced pluripotent stem cell (iPSC)‐derived BMEC‐like cells as a model BBB substrate on which to mine for new RMT‐targeting antibody pairs. A nonimmune, human single‐chain variable fragment (scFv) phage display library was screened for binding, internalization, and transcytosis across iPSC‐derived BMECs. Lead candidates exhibited binding and internalization into BMECs as well as binding to both human and mouse BBB in brain tissue sections. Antibodies targeted the murine BBB after intravenous administration with one particular clone, 46.1‐scFv, exhibiting a 26‐fold increase in brain accumulation (8.1 nM). Moreover, clone 46.1‐scFv was found to associate with postvascular, parenchymal cells, indicating its successful receptor‐mediated transport across the BBB. Such a new BBB targeting ligand could enhance the transport of therapeutic molecules into the brain.